2023
DOI: 10.52352/jarthy.v1i1.808
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Micro Business Enterprise Act on the Growth and Development of Micro-Entrepreneurs in the Province of Bataan, Philippines

Abstract: This research covers micro-entrepreneurs with BMBE certification in the Province of Bataan, Philipine. Impact assessment of BMBE will be measured in terms of profit maximization, increase capitalization, effective marketing tools, improve technology utilization and increased job generation. Questionnaires are provided to BMBE certificate holders to determine the level of impact on the growth and development of micro-entrepreneurs. The quantitative approach is employed for this study to understand the general c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Alera conducted a survey to BMBE owners in the Philippines to evaluate their awareness and utilization of the benefits provided by the BMBE Act (Alera, 2022). He found that while most BMBE owners are aware of the benefits, there is still low utilization, indicating a need for better information dissemination and advocacy.…”
Section: Difference On the Perceived Assessment On The Implementation...mentioning
confidence: 99%
“…Alera conducted a survey to BMBE owners in the Philippines to evaluate their awareness and utilization of the benefits provided by the BMBE Act (Alera, 2022). He found that while most BMBE owners are aware of the benefits, there is still low utilization, indicating a need for better information dissemination and advocacy.…”
Section: Difference On the Perceived Assessment On The Implementation...mentioning
confidence: 99%